The Relationship between Antibiotic Susceptibility and pH in the Case of Uropathogenic Bacteria - Annamária Kincses; Bálint Rácz; Zain Baaity; Orsolya Vásárhelyi; Erzsébet Kristóf; Ferenc Somogyvári; Gabriella Spengler (MDPI AG, 2021)
Urinary tract infections (UTIs) are common bacterial infections caused mainly by enteric bacteria. Numerous virulence factors assist bacteria in the colonization of the bladder. Bacterial efflux pumps also contribute to bacterial communication and to biofilm formation. In this study, the phenotypic and genetic antibiotic resistance of clinical UTI pathogens such as Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis were determined by disk diffusion method and polymerase chain reaction (PCR). Following this, different classes of antibiotics were evaluated for their antibacterial activity at pH 5, 6, 7 and 8 by a microdilution method. Gentamicin (GEN) was the most potent antibacterial agent against E. coli strains. The effect of GEN on the relative expression of marR and sdiA genes was evaluated by quantitative PCR. The slightly acidic pH (pH 6) and GEN treatment induced the upregulation of marR antibiotic resistance and sdiA QS activator genes in both E. coli strains. Consequently, bacteria had become more susceptible to GEN. It can be concluded that antibiotic activity is pH dependent and so the artificial manipulation of urinary pH can contribute to a more effective therapy of multidrug resistant bacterial infections.